Research on Maximum Efficiency Output Control of Voltage Controlled Adjustable Constant Current Source. Issue 1 (1st June 2022) - Yu, Yingbo; Kang, Zhongjian
Abstract: Voltage controlled adjustable constant current source has simple structure and high output precision, but its high switching power consumption and low output power efficiency under current variation hinder the development of its high current application. A maximum efficiency output control method of constant current source based on small signal model is presented to reduce switching loss and achieve high efficiency output. A 0-4A adjustable constant current source prototype was built to verify the theory, and the experimental results show that when the setting current changes from 1 to 4A, the output dynamic response of the experimental group is rapid, the instantaneous peak power of MOS transistor is only 6.04w, and compared with the control group, the average efficiency of the system is from 85.85% up to 92.86%, which indicate a better power consumption control ability.